دور شبكات التواصل الاجتماعي في تعزيز الهوية الوطنية لدى شباب الجزائري (دراسة ميدانية على بعض الطلبة الجامعيين مستخدمي الفيس بوك) - الذهبي, ابراهيم (جامعة الوادي - University of Eloued, 2019)
أضحت شبكات التواصل الاجتماعي مع انتشارها وتطورها تشكل حركة ديناميكية، أثرت ما يُطلق عليه حاليا الإعلام الجديد، الذي غير طبيعة العلاقات الاجتماعية، ورفع من وتيرة مشاركة الفرد في الحياة السياسية وبامتياز، خاصة بعد موجة التحول الديمقراطي العربي والتغيير السياسي، والتي ساهمت في ميلاد هوية وطنية للفرد تُساير وتُعزز مبادئ الديمقراطية والتحرر. و تهدف دراستنا إلى التعرف عن دور شبكات التواصل الاجتماعي في تعزيز الهوية الوطنية الجزائرية من حيث بعدي اللغة و الدين، في أوساط الشباب الجزائريين والطلبة الجامعيين خصوصا.Social networks became a dynamic movement, affecting what is now called the new media, which changed the nature of social relations and increased the pace of individual participation in political life and excellence, especially after the wave of Arab democratic transformation and political change, which contributed to the birth of a national identity The individual values and promotes the principles of democracy and emancipation. Our study aims to identify the role of social networks in promoting the Algerian national identity in terms of both language and religion, among Algerian youth and university students in particular.
The role of social networks in promoting the national identity of Algerian youth (a field study on some university students Facebook users)
مقال
Keywords: شبكات التواصل الاجتماعي، موقع الفيس بوك، الهوية الوطنية، الشباب الجامعي; Social networks ,Facebook ,National Identity ,University Youth